Perception knowledge and attitude of nursing students towards the care of older patients - Joel Olayiwola Faronbi; Olabisi Adebowale; Grace Oluwatoyin Faronbi; Oluwaseun Oluwafemi Musa; Sunday Joseph Ayamolowo (Elsevier, 2017)
The objectives of the study were to assess the perception, knowledge, and attitude of nursing students towards old age and care of the older adults and to examine personal characteristics that could predict their attitude.Two hundred and eighty students were systematically selected from learning institutions for nursing in Ile-Ife, Nigeria. Data on perception, knowledge, and attitude were collected with the aid of a validated self-administered questionnaire. Descriptive analysis and inferential statistics were done using Statistical Package for Social Sciences.Results showed that 66.1% and 71.8% of respondents had a positive perception and attitudes towards the care of older people, respectively. It further revealed that respondents believed that nurses should be patient, cheerful and sensitive (97.2%); as well as empathetic (91.4%) when caring for the older patients. The respondents also expressed that caring for the older patients goes beyond the basic nursing care (66.1%) and 90% supported the need for a geriatric unit in the hospital. Furthermore, 60% of respondents demonstrated good knowledge of essential clinical practice in the care of older patients. There was a statistically significant association between attitude and perception (ORÂ =Â 1.11; pÂ =Â 0.002) and age category 20â25 (ORÂ =Â 0.45; pÂ =Â 0.04). However, there was no significant association between the attitude of the respondents and knowledge (Ï2Â =Â 4.16; dfÂ =Â 2; pÂ =Â 0.125).The study concluded that the respondents have positive perception and attitude as well as good knowledge towards the care of the older adults. These should be reinforced to enhance a better clinical outcome in the care of the older adults. Keywords: Ageing, Attitude, Knowledge, Older adults, Perception